Integration of local wisdom based on Naskah Amanat Galunggung in civics learning - Yepy Agus Ramdani; Sapriya Sapriya (Faculty of Social and Political Science, Universitas Airlangga, 2017)
Indonesia as a developing country still faces with complex societal issues. To overcome these problems and to strengthen national identity one way is through the field of education. Education that takes into account the value of local wisdom will be easier to achieve educational goals. Naskah Amanat Galunggung contains the values of Sundanese wisdom that can be integrated into the Civic Education lesson. The location of the study was carried out on learning Civics in SMP Darul Falah 2 Cihampelas. The research method chosen is qualitative research using descriptive analytic method. In descriptive method of analytic data is collected as is then analyzed and given interpretation according to requirement of research. The results of this study indicates that the values contained in the Naskah Amanat Galunggung can be easily integrated into the Citizenship education as it is in accordance with the objectives of the Civic Education lesson. The integration of values of Amanat Galunggung in Civics Learning, especially in SMP Darul Falah 2 is by studying and inserting the local wisdom values in every Basic Competence.